EVALUASI KEMAMPUAN BENDUNGAN JLANTAH DALAM MEREDUKSI BANJIR - Siti Robiatul Adawiyah; Ignatius Sriyana; Suharyanto Suharyanto (Racic : Rab Construction Research, 2024)
The Jlantah Dam is a multi-purpose dam that was built in 2019. Besides the benefits, the dam also has potential danger if it floods and cause overtopping. Flood discharge is influenced by rainfall and land cover conditions. BMKG noted that the La Nina phenomenon occurred in 2020 – 2022 which had an impact on increasing rain intensity. Apart from that, from 2017 – 2023 there has been a change in land cover in the Jlantah Dam catchmen area. This research aims to analyze flood discharge at Jlantah Dam with current rain conditions and land cover and evaluate the safety of the dam against overtopping through HEC-HMS flood routing. The results of the HEC-HMS flood discharge analysis show that there is an increase in average flood discharge of ± 3,27% from the 2017 study. Based on the results of the flood routing, the dam's freeboard at discharge return periods 2, 5, 10, 25, 50, 100, 1000 years, and PMF respectively: 4,2 m; 3,9m; 3,8m; 3,5m; 3,3m; 3m; 2,6m; and 0,9m. At the PMF discharge there was a decrease in the freeboard of 0,35 m from the 2017 study but it remained safe against overtopping. The flood reduction at return periods 2, 5, 10, 25, 50, 100, 1000 years, and PMF respectively: 33%; 33%; 32%; 30%; 29%; 26%; 24%; and 17%.